2000
DOI: 10.1029/1999gl010767
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of energy transfer of Pi 2 magnetic pulsations: Latitudinal dependence

Abstract: Abstract. To investigate the generation and propagation mechanisms of Pi 2 magnetic pulsations, we have analyzed magnetic field data t?om the 210 ø magnetic meridian (MM) stations. We used 50 Pi 2 events that were simultaneously observed at seven stations along the 210 ø MM during January 1995, and tbcused our analysis on associated magnetic energy, ((/X/--D2+(AD)2)/kt 0. The times when the amplitude of the magnetic energy attained the maximum (T,,,,x) were compared among these stations. We tbund that T,,,,,. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 34 publications
(57 citation statements)
references
References 16 publications
(4 reference statements)
4
53
0
Order By: Relevance
“…This value is consistent with DT corr = −2 and 0 s for EWA and KAT. Numerical estimation by Uozumi et al [2000] showed that DTOF between equatorial and low-latitude stations was small values (few seconds for L < ∼2). According to the study by Yumoto [1990] cavitylike oscillation was observed at almost the same L value station SKD (L = 2.11) as KAT (L = 2.14).…”
Section: Interpretation Of the Present Pi2 Signatures By Applying Pasmentioning
confidence: 99%
“…This value is consistent with DT corr = −2 and 0 s for EWA and KAT. Numerical estimation by Uozumi et al [2000] showed that DTOF between equatorial and low-latitude stations was small values (few seconds for L < ∼2). According to the study by Yumoto [1990] cavitylike oscillation was observed at almost the same L value station SKD (L = 2.11) as KAT (L = 2.14).…”
Section: Interpretation Of the Present Pi2 Signatures By Applying Pasmentioning
confidence: 99%
“…The automated procedure from the 210 meridian magnetometer chain (see e.g. Uozumi et al, 2000) found Pi2 onset at ∼13:37 UT. In Fig.…”
Section: Event 1: 24 August 2001mentioning
confidence: 99%
“…In this way the escaping waves will have the same characteristics as those of the resonant field line. Uozumi et al (2000Uozumi et al ( , 2004 studied the latitudinal propagation of Pi2s. Statistically, they find that the average time delay of the maximum of the Pi2 wave power between CHD and MSR is a few seconds, with CHD leading.…”
Section: Pi2 Onset Sourcementioning
confidence: 99%
“…8) correspond to the cavity-mode oscillation of the plasmasphere in response to the above-presented hitting process, or to the propagation process itself of the Pi 2 signal within the plasmasphere, leaves room for argument, since we have no other satellites within the plasmasphere; ground observation only is not necessarily sufficient to separate out field-aligned travel time from radial travel time of Pi 2. For example, Uozumi et al (2000) statistically showed that Pi 2 signals propagating within the plasmasphere were observed earlier at smaller L on the ground (see their Fig. 3), unlike the one shown in this paper, and successfully explained it by their model cited above.…”
Section: Discussion and Summarymentioning
confidence: 63%
“…If we try to understand the observed phase pattern in terms of the Pi 2 propagation effect, we have to take into account the propagation time from Cluster to the ground along the magnetic field line. To calculate it, we use the procedure of Uozumi et al (2000Uozumi et al ( , 2007: we assume a cold plasma consisting of hydrogen ions and electrons, use the Tsyganenko 96 model for the magnetic field, use the model of Carpenter and Anderson (1992) for the equatorial plasma density, and use the power-law model for the field-aligned distribution of the plasma density n, i.e. n(r) = n eq (r/r eq ) −p , where r is the geocentric distance of any point on a field line, r eq is r on the equatorial plane, n eq is n there, and p is set to 3 (4) inside (outside) the plasmapause (Takahashi and Anderson, 1992).…”
Section: Discussionmentioning
confidence: 99%